Adaptive backstepping control of a speed-sensorless induction motor under time-varying load torque and rotor resistance uncertainty. (29th March 2010) - Ebrahim, Arbin; Murphy, Gregory
A new global adaptive backstepping controller is designed for induction motor speed control based on measurements of stator current and estimation of rotor speed. The designed partial state feedback controller is singularity free and guarantees asymptotic tracking of smooth reference trajectories for the speed of the motor under time varying load torque and rotor resistance uncertainty. The new control algorithm generates estimates for unknown time varying load torque, rotor resistance and rotor speed, which asymptotically tracks and converges to their true values. The rotor flux modulus asymptotically tracks a desired reference signal which allows the motor to operate within its specifications. As in the field-oriented control scheme; the control algorithm generates references for the magnetising flux component and for the speed component of the stator current. The control strategy yields decoupled rotor speed and rotor flux amplitude tracking control goals which allow the selection of an appropriate flux modulus for the rotor to maximise the efficiency.